2007
DOI: 10.1063/1.2777183
|View full text |Cite
|
Sign up to set email alerts
|

Nanomovement of azo polymers induced by metal tip enhanced near-field irradiation

Abstract: Nanomovement of azo polymers induced by metal tip enhanced near-field illumination was studied. A protrusion with 47nm full width at half maximum was induced with a resolution beyond the diffraction limit. At the top of the protrusion, an anisotropic movement occurs in a direction nearly parallel to the polarization of the incident light, and suggests the existence at the tip end of not only a longitudinal but also a lateral component of the electric field of light. The anisotropic photofluidity and the optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…(b) Pattern predicted by our model for the optimal value of the ratio c S =c 2 ¼ 4= (with c 1 =c 2 ¼ c 3 =c 2 ¼ À0: 15). (c) Pattern predicted by our model for c S ¼ 0 (vanishing surface effect).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Pattern predicted by our model for the optimal value of the ratio c S =c 2 ¼ 4= (with c 1 =c 2 ¼ c 3 =c 2 ¼ À0: 15). (c) Pattern predicted by our model for c S ¼ 0 (vanishing surface effect).…”
mentioning
confidence: 99%
“…The mass transport appears to occur preferentially in the direction of the electric field and to result from a photoinduced fluidization of the material [9][10][11][12][13]. These optical writing phenomena make azopolymers very attractive for optical data storage applications or for the nanoscale imaging of electromagnetic field distribution [14,15]. Recently, the potential advantage of using azopolymers in the place of sacrificial photoresists in the fabrication of silicon micro-and nanostructures has also been demonstrated [13,16].…”
mentioning
confidence: 99%
“…Boilot and coworkers and Fukuda and coworkers independently demonstrated that the formation of a nanoscale dot array and nano-characters was possible by a method using an optical fiber with a tiny aperture at the tip [123][124][125]. Sekkat and coworkers reported a silver-coated tip for an atomic force microscope that can generate an optical near-field spot, and can be used for near-field nanofabrication [126]. Furthermore, Karageorgiev and coworkers reported nano-manipulation by a method using the probe tip of a scanning force microscope.…”
Section: Micro-and Nanoscale Formationsmentioning
confidence: 99%
“…On the other hand, the areal density of the proposed devices under its present scheme is restricted by the diffraction limit. To overcome this limitation and increase the density, some more advanced scanning-probe approaches can be adopted, e.g., to induce nano-movement of azo copolymers by enhanced near-field irradiation 31 and to perform local PAP with scanning probes in azo copolymer. 27 The polar orientation of trans DR1 in copolymer is frozen at a temperature below T g , because rigid polymer main chains hinder the angular motion of DR1.…”
mentioning
confidence: 99%